DEVELOPING LEARNING MEDIA WITH ADOBE FLASH IN THE SUBJECT OF COMMUNICATION IN NETWORK FOR X GRADE OF VOCATIONAL HIGH SCHOOL - Pratama Benny Herlandy; Diah Eka Ratna; Edi Ismanto (PTE FTK UIN Ar-Raniry, 2019)
Learning with computer media that has not been multi-direction and lack of activeness of students makes learning less effective. Therefore, this study aims to develop learning media using Adobe Flash CS6, design and implement the development of instructional media on the subject of Communication in the Network, and test the feasibility of learning media. This research is a development research (R&D) with ADDIE model. The results of alpha testing, the assessment of material experts is in the very good category with an average score of 4.28. The assessment of media experts is in a very good category with an average score of 4.86. The results of the beta testing trial, the trial with the teacher, show a very good category with an average score of 5. Trials with students got a very good category with an average score of 4.25